Light Hadron Production in Proton-Proton Collisions at Different LHC Energies： Measured Data versus a Model - Guptaroy, P.; Guptaroy, S. (Chinese physics letters, 2014)
Experiments involving proton-proton collisions at energies √SNN=0.9, 2. 76 and 7 Te V in the large hadron collider produce a vast amount of high-precision data. In this work, we analyze two aspects of the measured data, viz., （i） the pT-spectra of pions, kaons, proton-antiproton at the above-mentioned energies, and （ii） some of their very important ratio behaviors, in the light of a version of the sequential chain model. The agreements between the measured data and the model-based results are generally found to be modestly satisfactory.